Associations among oral health-related quality of life, subjective symptoms, clinical status, and self-rated oral health in Japanese university students: a cross-sectional study. Issue 1 (December 2016) - Yamane-Takeuchi, Mayu; Ekuni, Daisuke; Mizutani, Shinsuke; Kataoka, Kota; Taniguchi-Tabata, Ayano; Azuma, Tetsuji; Furuta, Michiko; Tomofuji, Takaaki; Iwasaki, Yoshiaki; Morita, Manabu
Abstract Background The present study aimed to elucidate the associations among self-rated oral health, clinical oral health status, oral health behaviors, subjective oral symptoms, and oral health-related quality of life (OHRQoL) in a group of Japanese university students. Methods Of 2051 participants, 2027 (98.83%) students received an optional oral examination and answered a questionnaire including items regarding age, sex, self-rated oral health, oral health behaviors, subjective oral symptoms, and OHRQoL [The Oral Health Impact Profile (OHIP)-14]. On oral examination, the decayed, missing, and filled teeth (DMFT) score, Community Periodontal Index (CPI), the percentage of teeth showing bleeding on probing (%BOP), and malocclusion were recorded. Structural equation modelling (SEM) analysis was used to test associations. Results The mean score (± SD) of OHIP-14 was 1.92 ± 5.47. In the SEM analysis, the final model showed that self-rated oral health, oral pain, malocclusion, and the DMFT score were directly associated with the OHRQoL, and subjective symptoms of temporomandibular disorders (TMD) and recurrent aphthous stomatitis were both directly and indirectly associated (p  < 0.05). CPI, %BOP, and oral health behaviors were excluded from the final model. Conclusions OHRQoL was associated with self-related oral health, subjective symptoms of TMD, oral pain and stomatitis, DMFT, and malocclusion in this group of Japanese university students.